Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Polaronic deformation at theFe2+/3+impurity site inFe:LiNbO3crystals - Sanson, A.; Zaltron, A.; Argiolas, N.; Sada, C.; Bazzan, M.; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Influence of Structural Defects and Oxidation onto Hole Conductivity in P3HT - Lücke, A.; Schmidt, Wolf Gero; Rauls, E.; Ortmann, F.; Gerstmann, Uwe (The Journal of Physical Chemistry B)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Nanopatterning on H-Terminated Si(111) Explained as Dynamic Equilibrium of the Chemical Reaction with Methanol - Thissen, Peter; Fuchs, Ehud; Roodenko, Katy; Peixoto, Tatiana; Batchelor, Ben; Smith, Dennis; Schmidt, Wolf Gero; Chabal, Yves (The Journal of Physical Chemistry C)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

The Cu2O2torture track for a real-life system: [Cu2(btmgp)2O2]2+oxo and peroxo species in density functional calculations† - Rohrmüller, Martin; Hoffmann, Alexander; Thierfelder, Christian; Herres-Pawlis, Sonja; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Water adsorbate influence on the Cu(110) surface optical response - Baghbanpourasl, Amirreza; Schmidt, Wolf Gero; Denk, Mariella; Cobet, Christoph; Hohage, Michael; Zeppenfeld, Peter; Hingerl, Kurt (Surface Science)

A quantum dot single-photon source with on-the-fly all-optical polarization control and timed emission - Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Schumacher, Stefan (Nature Communications)
Sources of single photons are key elements for applications in quantum information science. Among the different sources available, semiconductor quantum dots excel with their integrability in semiconductor on-chip solutions and the potential that photon emission can be triggered on demand. Usually, the photon is emitted from a single-exciton ground state. Polarization of the photon and time of emission are either probabilistic or pre-determined by electronic properties of the system. Here, we study the direct two-photon emission from the biexciton. The two-photon emission is enabled by a laser pulse driving the system into a virtual state inside the band gap. From this intermediate state, the single photon of interest is then spontaneously emitted. We show that emission through this higher-order transition provides a versatile approach to generate a single photon. Through the driving laser pulse, polarization state, frequency and emission time of the photon can be controlled on-the-fly.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Subpicosecond Exciton Dynamics in Polyfluorene Films from Experiment and Microscopic Theory - Denis, Jean-Christophe; Schumacher, Stefan; Hedley, Gordon J.; Ruseckas, Arvydas; Morawska, Paulina O.; Wang, Yue; Allard, Sybille; Scherf, Ullrich; Turnbull, Graham A.; Samuel, Ifor D. W.; Galbraith, Ian (The Journal of Physical Chemistry C)

A population-competition model for analyzing transverse optical patterns including optical control and structural anisotropy - Tse, Y C; Chan, Chris K P; Luk, M H; Kwong, N H; Leung, P T; Binder, R; Schumacher, Stefan (New Journal of Physics)

How intermolecular geometrical disorder affects the molecular doping of donor–acceptor copolymers - Di Nuzzo, Daniele; Fontanesi, Claudio; Jones, Rebecca; Allard, Sybille; Dumsch, Ines; Scherf, Ullrich; von Hauff, Elizabeth; Schumacher, Stefan; Da Como, Enrico (Nature Communications)

All-optical flow control of a polariton condensate using nonresonant excitation - Schmutzler, Johannes; Lewandowski, Przemyslaw; Aßmann, Marc; Niemietz, Dominik; Schumacher, Stefan; Kamp, Martin; Schneider, Christian; Höfling, Sven; Bayer, Manfred (Physical Review B)

It’s the situation that matters: Affective involvement in context-oriented learning tasks - Fechner, Sabine; Van Vorst, Helena; Kölbach, Eva; Sumfleth, Elke (Affective Dimensions in Chemistry Education)

Charakterisierung und Strukturierung von Kontexten im naturwissenschaftlichen Unterricht – Vorschlag einer theoretischen Modellierung - van Vorst, Helena; Dorschu, Alexandra; Fechner, Sabine; Kauertz, Alexander; Krabbe, Heiko; Sumfleth, Elke (Zeitschrift für Didaktik der Naturwissenschaften)

Mit Leitungswasser eine Uhr betreiben? Eine alternative Herangehensweise an die Elektrochemie - Fechner, Sabine; Dettweiler, Yvonne (Naturwissenschaften im Unterricht - Chemie)

A panel of peralkylated sulfur–guanidine type bases: Novel pro-ligands for use in biomimetic coordination chemistry - Neuba, Adam; Rohrmüller, Martin; Hölscher, Rebecca; Schmidt, Wolf Gero; Henkel, Gerald (Inorganica Chimica Acta)

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)